The Effect of Muslim Lifestyle Knowledge on Motivation Use of Dental Braces in Adolescents (Study of Students SMAI Al-Azhar Kelapa Gading) - Sekar, Meisa Sabrina; Niam, Moh Husnun; Ardlina, Nira (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Knowledge of Muslim lifestyle is the understanding of a Muslim which arieses from its application from the learning process and experience that comes from the environment, parents or offspring, social and culture and so on including lifestyle in accordance with the advice of Islam based on the Al-Quran and Hadits.Methods: Many teenegers have a level of awareness to maintain healthy teeth and mouth, one of which is dental braces treatment. For teenegers, the use of braces can improve facial appearance because facial appearance is a very important aspect of physical appearance. Result: Teenager’s motivation is based on good knowledge of the Muslim lifestyle, so the teenager also has better motivation compared to teenegers who do not have sufficient knowledge of the Muslim lifestyle.Conclusion: from the results of the Spearman correlation test is positive, which means that the relationship between theses variables is straight or positive, that is, the higher the knowledge of Muslim lifestyle, the higher the motivation to use braces in adolescents.